Assessment of Leishmanicidal and Trypanocidal Activities of Aliphatic Diamine Derivatives. (10th August 2013) - Yamanaka, Celina N.; Giordani, Raquel B.; Rezende, Celso O.; Eger, Iriane; Kessler, Rafael L.; Tonini, Maiko L.; de, Milene H.; Araújo, Debora P.; Zuanazzi, Jose A.; de, Mauro V.; Steindel, Mario
<x xml:space="preserve">Abstract</x> Leishmanicidal and trypanocidal activity of seventeen lipophilic diamines was evaluated in vitro against Leishmania braziliensis, L. chagasi, and Trypanosoma cruzi. Twelve compounds presented anti‐Leishmania and six showed anti‐T. cruzi amastigote activity. Compound 14 (N‐tetradecyl‐1, 4‐butanediamine) was the most active against both L. braziliensis (IC50 = 2.6 μm) and L. chagasi (IC50 = 3.0 μm) which showed a selectivity index (SI) >100. N‐decyl‐1, 6‐hexanediamine (compound 9) presented an IC50 = 1.6 μm and SI >187 and was over six times more potent than the reference drug benznidazole against T. cruzi. Treatment of infected or uninfected macrophages with compounds 9 and 14 did not induce significant TNFα and NO production. Four compounds (15, 16, 22, and 23) inhibited 78.9%, 77.7%, 83.7%, and 70.1% of rTRLb activity, respectively, and compound 23 inhibited 73.3% of rTRTc activity at 100 μm. A concentration‐dependent effect on mitochondrial membrane depolarization was observed in T. cruzi epimastigotes treated with compound 9, suggesting this mechanism may be involved in the trypanocidal effect. On the contrary, in L. braziliensis promastigotes treated with compound 14, no mitochondrial depolarization was observed. Our results demonstrate that N‐decyl‐1, 6‐hexanediamine and N‐tetradecyl‐1, 4‐butanediamine are promising molecules for the development of novel leading compounds against T. cruzi and Leishmania spp., particularly given a possible alternative mechanism of action.